Age-related changes in cardio-respiratory responses and muscular performance following an Olympic triathlon in well-trained triathletes - Sultana, F.; Abbiss, C. R.; Louis, J.; Bernard, T.; Hausswirth, C. (European Journal of Applied Physiology, 2012)
The aim of the present study was to compare the maximal isometric torque and cardio-respiratory parameters in well-trained young and master triathletes prior to and following an Olympic distance triathlon. One day before and 24 h following the event, participants performed three maximum voluntary isometric knee extensions and flexions and an incremental running test on a treadmill to determine the maximal isometric torque, maximal oxygen uptake VO(2max), speed at VO(2max) (vVO(2)max), speed at ventilatory thresholds (VT1 and VT2) and submaximal running economy. Prior to the event VO(2max), vVO(2)max, speed at ventilatory thresholds and running economy were significantly lower in master athletes, but maximal voluntary torque was similar between the groups. 24 h following the race, a similar significant decrease in VO(2max) (-3.1% in masters, and -6.2% in young, p < 0.05), and vVO(2)max (-9.5% in masters, and -5.6% in young, p < 0.05) was observed in both the groups. The speed at VT2 significantly decreased only in master athletes (-8.3%, p < 0.05), while no change was recorded in maximal voluntary torque or submaximal running economy following the event. The results indicate that for well-trained subjects, the overall relative exercise intensity during an Olympic distance triathlon and the fatigue 24 h following the event seem to be independent of age.